Analisis Pengendalian Kualitas Sheet Mask dengan Metode SQC di PT X - I Gusti Ngurah Priambadi; Ni Made Cyntia Utami; I Made Dwi Budiana Penindra; Desak Ayu Sista Dewi; Bryan Estavan Imanuel Sitanggang; Makarawung, Advenni Natalia (Study Program of Industrial Engineering, Udayana University, 2023)
PT X is a manufacturing industry company engaged in cosmetic and skincare manufacturing services that produce products based on order or PO (pre-order). In the production process carried out by PT X, there are several product defects such as damaged masks, packaging, and so on so that the product is not suitable for use and reaches consumers, for that the importance of the production process control system in a company in identifying factors causing damage or defects in sheet mask products and analyzing how to apply statistical quality control in quality control at PT X. The results of the pareto chart analysis with the most frequent problems to get priority for repair, namely the type of plastic defect (53%). Based on the P-chart analysis the production process is still not under control or still experiencing deviations, this is shown on the P-chart that many points are beyond the control limit. Known from the results of diagram analysis fishbone related factors causing plastic defects come from human, machine, and material factors. Companies should conduct training for employees on the shrink process, conduct regular checks on production machines and replace plastic materials that are thicker than before.